2019
DOI: 10.3390/s19204465
|View full text |Cite
|
Sign up to set email alerts
|

RF Energy Harvesting IoT System for Museum Ambience Control with Deep Learning

Abstract: Museum contents are vulnerable to bad ambience conditions and human vandalization. Preserving the contents of museums is a duty towards humanity. In this paper, we develop an Internet of Things (IoT)-based system for museum monitoring and control. The developed system does not only autonomously set the museum ambience to levels that preserve the health of the artifacts and provide alarms upon intended or unintended vandalization attempts, but also allows for remote ambience control through authorized Internet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
(93 reference statements)
0
17
0
Order By: Relevance
“…The authors in [200] and [201] use electric power data and heat flow information in a building to predict the energy requirements in the future so as to better manage energy consumption. Ambience control of a museum has been performed in [202] where the authors use deep learning algorithms to predict the CO 2 and humidity levels for the care of exhibits. Comfort aware energy management has been performed in [203] where the authors use a CNN to regulate thermal comfort in a building using various physical quantities.…”
Section: Smart Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [200] and [201] use electric power data and heat flow information in a building to predict the energy requirements in the future so as to better manage energy consumption. Ambience control of a museum has been performed in [202] where the authors use deep learning algorithms to predict the CO 2 and humidity levels for the care of exhibits. Comfort aware energy management has been performed in [203] where the authors use a CNN to regulate thermal comfort in a building using various physical quantities.…”
Section: Smart Industrymentioning
confidence: 99%
“…SAE [201] Regression-Energy predictions for buildings Homogeneous (Heat flow data in buildings) RNN (GRU, LSTM) [202] Regression-Prediction of environmental variables (CO 2 , Humidity etc. )…”
Section: Smart Industrymentioning
confidence: 99%
“…Based on a review of the past literature in this area [61 -63], we found that RF waves energy harvesting is the best solution in many scenarios when it comes to low-energy IoT devices. The works in [64,65] and [66] highlight the potential of using RF Energy Harvesters (RFEHs) to power IoT devices for environmental and healthcare monitoring. Other approaches for harvesting energy from RF signals include opportunistic charging from nearby smartphones [67], or the sharing of energy between different wireless systems close to each other [68].…”
Section: Rf Energy Harvestingmentioning
confidence: 99%
“…In general, small electronic devices with minimum power consumption requirements (e.g., WSN's node), can be powered from ambient RF Energy. The applicability of the proposed improved version of storage-based RF energy harvesting system could be the power supply of a WSN's node for Internet of Things (IoT) applications [27]. A WSN' node can be self-powered from ambient RF energy by the storage-based harvester when the "wake-up" mode is active (e.g., for wireless data transmission).…”
Section: Evaluation Of Measurements and Applicabilitymentioning
confidence: 99%